UPAYA KONSERVASI JENIS ANGGREK DAN KANTONG SEMAR DI DEMPLOT ANGGREK SOBLEMAN, RESORT WONOLELO DARI KEPUNAHAN - Bebi Sylvia Muryanto; Danastri Nur Athaya Radya Putri (Yayasan Nusantara Hasana Berdikari, 2023)
One of the important natural resources for human life is the forest. In the forest, there is a complex structure that will create an environment so that various types of plants grow in it, among the plants that grow in the forest are orchids and kantong semar plants. The results showed that there were 22 types of orchids and one type of kantong semar plants found and cultivated. The cultivation technique used is the split technique (vegetative) and natural pollination (generative), which is the growth of flower seeds that fall on the planting media. Data collection was carried out using observation methods, interviews with officers in charge of demonstration plots, and literature studies. The purpose of this research is to find out the efforts made for the conservation of orchids and kantong semar plants in Wonolelo Resort. In addition, this study aims to determine the types of Orchids in the Wonolelo Resort Orchid demonstration plot.